The utility and safety of ureteral access sheath during retrograde intrarenal surgery in children - TANIDIR, YILÖREN (My University, 2023)
Objectives: The objectives of this study are to present our experience with retrograde intrarenal surgery for management of renal calculi in children less than 7 years old and to determine its safety and efficacy in this age group. Methods: Patient demographics, stone location and size, use of ureteral access sheath, stone-free status, complication rates, and follow-up were evaluated. Results: A total of 16 patients (9 boys and 7 girls; mean age, 4.2 years) underwent 17 procedures. The mean stone size was 11.5 mm (8-17 mm). Flexible ureteroscopy and laser lithotripsy were performed in all cases regardless of stone location. Dilation of the ureteral orifice was required in 5 cases (29.4%), and ureteral access sheaths were placed in 3 patients (17.6%). With a mean follow-up of 10.3 months, 88% of the children were stone free. The success rate for stones less than 10 mm was 100% and 81.8% for stones 10 mm or more (P b .05). There were no major complications, but there was 1 case of perforation and extravasation at the ureterovesical junction after balloon dilation that was managed with stent placement. Conclusions: Retrograde intrarenal surgery is a safe and effective method for the treatment of intrarenal calculi, and it achieves reasonable results with minimal complications in children less than 7 years old. © 2011 Elsevier Inc. All rights reserved.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; Children; Renal stone; Retrograde intrarenal surgery; Ureteroscopy